Editorial: Traffickers - McAdam, Marika; Gerasimov, Borislav (Anti-Trafficking Review, 2022)
This article introduces a Special Issue of Anti-Trafficking Review themed ‘Traffickers’. It describes how most of the knowledge about human trafficking is generated from the accounts of victims of trafficking and people working with them, while knowledge of perpetrators of human trafficking remains limited. It further summarises the articles contained in this special issue. These articles describe one or more aspects of traffickers’ characteristics, motivations, modus operandi, relationships with victims, and treatment in the criminal justice system. Overall, the issue shows that in many cases, traffickers’ profiles are similar to those of their victims. It suggests that measures to reduce racial, ethnic and other discrimination and improve socioeconomic and educational opportunities for all would help reduce people’s vulnerability to becoming victims of trafficking as well as perpetrators.